Pilot Research into the Perceived Importance of Educational Elements and an Application for Detecting Progress through the Perspective of Practice - Kateřina Berková; Dagmar Frendlovská; Martina Chalupová; Andrea Kubišová; Roman Hrmo; Katarína Krpálková Krelová (MDPI AG, 2022)
Data analysis and the development of learning skills based on monitoring students' progress are aspects in demand by schools and students. Quite a lot of studies deal with Learning Analytics Dashboards. There is a limited number of studies that take into account the supply of such tools on the market. In this pilot study, the researchers present findings on the attitudes of 19 higher education institutions from the Czech Republic, Belgium, Germany, Greece, the Netherlands and Poland, along with 14 secondary schools from the Czech Republic, towards the proposed web-based application for supporting learning and providing automated feedback on student progress in accounting education. The aim of this section was to find out how schools perceive the importance of the proposed application and its specific parameters. The study also presents the current product offer on the Czech market and the interest among 112 companies in developing such an application. The findings revealed that there is no such tool offered on the Czech market, and the majority of the analyzed companies are interested in its development. The schools evaluated the learning tool as being most important in the area of distance learning, and most useful for the visualization of accounting methods based mainly on imagination. The value of such an application is seen in supporting self-study, providing information on attitudes and current abilities, and tracking students' learning progress.